Reinforcer pathology II: Reward magnitude, reward delay, and demand for alcohol collectively relate to college students' alcohol related problems. Issue 3 (12th November 2020) - Stancato, Stefanie S.; Schneider, Tadd D.; Reed, Derek D.; Lemley, Shea M.; Carrillo, Ale; Jarmolowicz, David P.
Abstract : The reinforcer pathologies model of addiction posits that two characteristic patterns of operant behavior characterize addiction. Specifically, individuals suffering from addiction have elevated levels of behavioral economic demand for their substances of abuse and have an elevated tendency to devalue delayed rewards (reflected in high delay discounting rates). Prior research has demonstrated that these behavioral economic markers are significant predictors of many of college students' alcohol‐related problems. Delay discounting, however, is a complex behavioral performance likely undergirded by multiple behavioral processes. Emerging analytical approaches have isolated the role of participants' sensitivity to changes in reinforcer magnitude and changes in reinforcer delay. The current study uses these analytic approaches to compare participants' discounting of money versus alcohol, and to build regression models that leverage these new insights to predict a wider range of college students' alcohol related problems. Using these techniques, we were able to 1) demonstrate that individuals differed in their sensitivity to magnitudes of alcohol versus money, but not sensitivity to delays to those commodities and 2) that we could use our behavioral economic measures to predict a range of students' alcohol related problems.